KONSEP AKSIOLOGI DALAM MENINGKATKAN NILAI PENDIDIKAN ISLAM - Salsabila, Salwa Atika; Rianti, Indhi; Anjani, Ananda Ainia; Muhsonawawi, Muhammad; El-Yunasi, Muhammad Yusron (Jurnal Al-Fatih, 2024)
Axiology may be a department of logic that thinks about values and is one of the hypothetical establishments within the ponder of logic of science that underpins the advance of science. The strategy utilized is writing look or writing ponder. This strategy includes looking for different pertinent sources, such as books, diary articles, and other distributions related to the subject of the concept of axiology in expanding the esteem of Islamic instruction. With a add up to of 9 books, and 12 diary articles downloaded on Google researcher and semantic researcher with the keywords philosophy of Islamic instruction, educational modules advancement with a time span of 2023-2016. The steps within the writing look technique incorporate: Theme Recognizable proof, Catchphrase Determination, Source Look, Source Determination, and Article Writing Education may be a cognizant exertion to direct understudy development and improvement. Usually done intentioned and arranged through a prepare of mentoring, instructing, preparing, and habituation that can make an environment and learning process that empowers understudies to effectively create their potential and identity capacities to attain development, which is characterized as having the insights, ethical quality, self-control, and development required for themselves, society, and the state. This could be done interior or exterior of school and endures for a lifetime. Axiology is a department of logic that looks at and analyzes the nature of ni.